1996
DOI: 10.1210/jcem.81.12.8954028
|View full text |Cite
|
Sign up to set email alerts
|

Effects on bone mass of long term treatment with thyroid hormones: a meta-analysis.

Abstract: Osteoporosis is the main cause of spine and hip fractures. Morbidity, mortality, and costs arising from hip fractures have been well documented. Thyroid hormones (TH) are widely prescribed, mainly in the elderly. Some studies (but not all) found a deleterious effect of suppressive TH therapy on bone mass. These conflicting data raised a controversy as to the safety of current prescribing and follow-up habits, which, in turn, raised major health-care issues. To look for a detrimental effect on bone of TH therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
15

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(116 citation statements)
references
References 58 publications
5
96
0
15
Order By: Relevance
“…Similar results were found in longitudinal studies with decreased or normal bone mineral density in pre-(92 -94) or postmenopausal women (72, 91, 92 -95) with exogenous subclinical hyperthyroidism. Indeed, in two meta-analyses, exogenous subclinical hyperthyroidism was associated with a significant bone loss in post-but not in premenopausal women (96,97).…”
Section: Bone Structure and Metabolismmentioning
confidence: 99%
“…Similar results were found in longitudinal studies with decreased or normal bone mineral density in pre-(92 -94) or postmenopausal women (72, 91, 92 -95) with exogenous subclinical hyperthyroidism. Indeed, in two meta-analyses, exogenous subclinical hyperthyroidism was associated with a significant bone loss in post-but not in premenopausal women (96,97).…”
Section: Bone Structure and Metabolismmentioning
confidence: 99%
“…Poderse-ia especular que o tratamento com doses de l-T 4 discretamente maiores pudesse refletir nos valores de DMO dos pacientes em relação ao grupo controle, uma vez que, conforme a metanálise de Uzzan e cols. (30), o excesso de HT aumenta o turnover ósseo e diminui a massa óssea. Como, por questões éticas, não foi dosado TT 4 nas crianças do grupo controle, a relação entre DMO e valor de TT 4 no grupo A é hipotética, pois não se encontrou correlação entre as médias da dose de l-T 4 , TSH, TT 4 e FT 4 durante todo o seguimento e as médias de DMO e CMO dos pacientes.…”
Section: Parâmetrounclassified
“…Despite publication in the last decade of several studies (Franklyn et al 1992, Kung et al 1993, Giannini et al 1994, Marcocci et al 1994, McDermott et al 1995, Muller et al 1995, Rosen et al 1998) and meta-analyses on this topic (Faber & Galloe 1994, Uzzan et al 1996, evidence that subclinical hyperthyroidism affects skeletal integrity and is therefore a risk factor for osteoporosis, is inconclusive (Greenspan & Greenspan 1999, Toft 2001, Quan et al 2002, Murphy & Williams 2004. The meta-analyses and systematic reviews reported either a decrease in bone mineral density during prolonged subclinical hyperthyroidism, mainly in postmenopausal women, or no changes (Faber & Galloe 1994, Uzzan et al 1996, Greenspan & Greenspan 1999, Lau et al 2001, Toft 2001, Quan et al 2002, Murphy & Williams 2004. Among premenopausal women, the effect does not appear to be significant (Marcocci et al 1994).…”
Section: Introductionmentioning
confidence: 99%